eCM 2014
DOI: 10.22203/ecm.v027a11
|View full text |Cite
|
Sign up to set email alerts
|

Chondrogenically differentiated mesenchymal stromal cell pellets stimulate endochondral bone regeneration in critical-sized bone defects

Abstract: Grafting bone defects or atrophic non-unions with mesenchymal stromal cells (MSCs)-based grafts is not yet successful. MSC-based grafts typically use undifferentiated or osteogenically differentiated MSCs and regenerate bone through intramembranous ossification. Endochondral ossification might be more potent but requires chondrogenic differentiation of MSCs. Here, we determined if chondrogenically differentiated MSC (ch-MSC) pellets could induce bone regeneration in an orthotopic environment through endochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 34 publications
1
72
1
Order By: Relevance
“…As we know, chondrogenic cells commonly begin hypertrophic differentiation after 21 d [28][29][30][31], and we also showed that the hypertrophic marker Col10a1 was significantly increased after 21 d of chondrogenic differentiation; thus, miR-455-3p might be involved in the acceleration of early chondrogenesis, but not hypertrophic differentiation.…”
Section: Discussionmentioning
confidence: 66%
“…As we know, chondrogenic cells commonly begin hypertrophic differentiation after 21 d [28][29][30][31], and we also showed that the hypertrophic marker Col10a1 was significantly increased after 21 d of chondrogenic differentiation; thus, miR-455-3p might be involved in the acceleration of early chondrogenesis, but not hypertrophic differentiation.…”
Section: Discussionmentioning
confidence: 66%
“…Another limitation of this study is the use of ascorbic acid and dexamethasone in the chondrogenic medium, which might be expected to cause MSCs to differentiate toward the osteogenic lineage. However, the use of dexamethasone and ascorbic acid in the chondrogenic medium is well documented 53,60,66,78,[91][92][93][94][95][96][97][98][99][100][101][102] and has not been shown to cause mineralization. Moreover, alizarin red staining of the aggregates before the coculture showed no positive staining and the control groups were all exposed to the same chondrogenic medium, so any differences seen between the groups were not because of exposure to these growth factors.…”
Section: Discussionmentioning
confidence: 99%
“…61,67,70,71,75 Most of these studies utilized a heterotopic bone formation model in immunocompromised animals to provide evidence of osteo-and chondro-conductivity and inductivity. However, more recent studies by Bahney et al, 110 van der Stok et al, 106 Harada et al, 105 and Shoji et al 108 (Table 2) showed critical-size defect regeneration in rat femurs and mice tibias via EC ossification. Likewise, studies by Montufar-Solis et al 27 and Doan et al 62 (Table 3) showed critical-sized defect regeneration in murine calvaria.…”
Section: Incorporating Scbts Into the Designmentioning
confidence: 97%
“…[1][2][3][4][5][6][7][8][9] An emerging group of successful research efforts have focused on exploiting this condition over the past decade. These recent publications (Tables 2-4) have demonstrated the capacity of cartilage tissue constructs to promote EC ossification in vivo after in vitro priming with seeded BMSCs, 60,63,64,66,67,[72][73][74][75][76][103][104][105][106][107] ESCs, 27,62,67,76 ADSCs, 108 iPSCs, 109 and articular chondrocytes (ACs). 61,67,70,71,75 Most of these studies utilized a heterotopic bone formation model in immunocompromised animals to provide evidence of osteo-and chondro-conductivity and inductivity.…”
Section: Incorporating Scbts Into the Designmentioning
confidence: 99%